Overcoming Ploidy Barriers: The Role of Triploid Bridges in the Genetic Introgression of Cardamine amara - Bartolić, P; Voltrová, A; Macková, L; Šrámková, G; Šlenker, M; Mandáková, T; Padilla García, N; Marhold, K; Kolář, F (Molecular ecology, 2025)
Polyploidisation is a significant reproductive barrier, yet genetic evidence indicates that interploidy admixture is more common than previously thought. Theoretical models and controlled crosses support the 'triploid bridge' hypothesis, proposing that hybrids of intermediate ploidy facilitate gene flow. However, comprehensive evidence combining experimental and genetic data from natural mixed-ploidy species is missing. Here, we investigated the rates and directionality of gene flow within a diploid-autotetraploid contact zone of Cardamine amara, a species with abundant natural triploids. We cytotyped over 400 individuals in the field, conducted reciprocal interploidy crosses, and inferred gene flow based on genome-wide sequencing of 84 individuals. Triploids represent a conspicuous entity in mixed-ploidy populations (5%), yet only part of them arose through interploidy hybridisation. Despite being rarely formed, triploid hybrids can backcross with their parental cytotypes, producing viable offspring that are often euploid (in 42% of cases). In correspondence, D-statistics and coalescent simulations documented a significant genome-wide signal of bidirectional gene flow in sympatric but not allopatric populations. Triploids, though rare, thus seem to play a key role in overcoming polyploidy-related reproductive barriers in C. amara. In sum, we present integrative evidence for interploidy gene flow mediated by a triploid bridge in natural populations.
Keywords: hybridizace genetická; Triploidy; tok genů; Ploidies; Gene Flow; polyploidie; Polyploidy; triploidie; polyploidy; ploidie; Hybridization, Genetic; whole genome duplication; Genetics, Population; population genomics; speciation; Cardamine; Genetic Introgression; genová introgrese; populační genetika; introgression